Egoistic and ethical orientations of university students toward work-related decisions - Shepard, Jon M. (Journal of business ethics, 1991)
An onslaught of ethically questionable actions by top government, business, and religious leaders during the 1980s has brought the issue of ethics in decision making to the forefront of public consciousness. This study examines the ethical orientation of university students in four decision-making situations. The dependent variable — ethical orientation toward work-related decisions — is measured through student responses to questions following four work-related vignettes. Possible responses to each vignette are structured to permit categorization of respondents into two broad orientations: egoistic and ethical. Independent variables are academic major, “ethics in business orientation,” gender, and religiosity. Generally, students tended to choose an ethical orientation over an egoistic orientation in each vignette. Business majors were generally no less likely to choose an ethical orientation toward work-related decisions than nonbusiness majors. Respondents characterized by “moral unity” (belief in the consistency between general ethical principles and work-related ethical standards) were more likely to have an ethical orientation toward work-related decisions than those subscribing to the “amoral theory of business.” Females showed a consistent tendency to be more ethically oriented toward work-related decisions than males. Finally, respondents high on religiosity tended to be more ethically oriented.